Biofabrication of AuNPs using Coriandrum sativum leaf extract and their antioxidant, analgesic activity - Jiao, Yang; Wang, Xinglei; Chen, Ji-hua (The Science of the total environment, 2021)
In this work, Gold nanoparticles (AuNPs) were synthesized by reducing aqueous Au metal ions upon interaction with Coriandrum sativum (C. sativum) leaf extract. The optical absorption peak for the synthesized AuNPs was obtained by using UV–visible spectroscopy within a range of 540–550 nm. The formation of diffraction peaks found at 2θ values of 78.00°, 66.05°, 44.85° and 38.48° that corresponds to the index planes (311), (220), (200), and (111) validate the effective synthesis of AuNPs. Transmission electron microscopy (TEM) was utilized to measure the size range of the spherical shaped nanoparticles, which is obtained to be 32.96 ± 5.25 nm. The peaks obtained from the FTIR results are closely linked to anthocyanins, benzophenones, flavonoids and phenols, which indicated that these biomolecules may serve as reducing agents. Additionally, studies of antioxidant function in vitro revealed that the activities of ABTS (2, 2′-azino-bis 3-ethylbenzthiazoline-6-sulfonic acid) and DPPH (2,2-diphenyl-1-picrylhydrazyl) were improved dose-dependently. Further, the results of analgesic analysis showed that the cumulative action of AuNPs and the C. sativum leaf extract in pain relief is more efficient than independent C. sativum leaf extract and the aspirin drug. [Display omitted] •Coriandrum sativum leaf extract mediated synthesis of AuNPs•Dose dependent antioxidant activity of AuNPs•Synergistic action of AuNPs and C. sativum polyphenols in pain relief